Städtenetze als raumordnungspolitischer Handlungsansatz: Gefährdung oder Stütze des Zentrale-Orte-Systems? - Priebs, Axel (ERDKUNDE, 1996)
The article deals with the relationship between urban networks as a new instrument of spatial planning. The latter is seen as the basic structure in space, which guarantees especially in rural areas - a minimum of public services and thus equivalent living conditions. Urban networks, as being in the general rule the spontaneous cooperation of neighbouring municipalities, are to be regarded as positive. However, successful networks can interfere in the basic structure of the central pi ace system. This is acha11enge for regional planning to take up the position of a mediator to prevent the emergence of disadvantaged remnant areas. A normative definition of urban networks by regional planning is to be seen critically, because urban networks can hardly be successful without bottom-up initiatives.